Significant atmospheric aerosol pollution caused by world food cultivation. Issue 10 (16th May 2016) - Bauer, Susanne E.; Tsigaridis, Kostas; Miller, Ron
Abstract: Particulate matter is a major concern for public health, causing cancer and cardiopulmonary mortality. Therefore, governments in most industrialized countries monitor and set limits for particulate matter. To assist policy makers, it is important to connect the chemical composition and severity of particulate pollution to its sources. Here we show how agricultural practices, livestock production, and the use of nitrogen fertilizers impact near‐surface air quality. In many densely populated areas, aerosols formed from gases that are released by fertilizer application and animal husbandry dominate over the combined contributions from all other anthropogenic pollution. Here we test reduction scenarios of combustion‐based and agricultural emissions that could lower air pollution. For a future scenario, we find opposite trends, decreasing nitrate aerosol formation near the surface while total tropospheric loads increase. This suggests that food production could be increased to match the growing global population without sacrificing air quality if combustion emission is decreased. Key Points: PM2.5 from agricultural sources dominate over nonagricultural and naturally occurring PM2.5 By the end of the century, agriculture‐driven aerosol formation will be reduced near to the Earth surface Source‐receptor scenarios of emission reduction are testing ammonia versus nitrogen oxide reductions